Learning by Comparison: The Benefits of Co-Teaching for University Professors’ Professional Development - Buckingham, Lyndsay R.; López-Hernández, Alfonso; Strotmann, Birgit (Frontiers in Education, 2021)
There is an abundance of studies that suggest that the use of co-teaching strategies in higher education courses can enhance instructors’ professional development, mainly by providing a space for transfer of methodologies and tools, as well as critical reflection on one’s teaching practice. However, little has been said about the actual processes through which co-teachers learn from each other. This study analyzes the opportunities of professional growth afforded to seven professors by eight co-taught courses, over two academic years, in the fields of Education and Translation and Interpreting. Specifically, it examines how professional relationships between co-teachers fuel teacher learning, the specific learning processes generated, and the areas of professional development impacted. To do so, eleven reflective teacher diaries were coded and analyzed, and further evidence was collected through focus groups interviews with students of some of the co-taught courses. Results suggest that comparison with the co-teacher is the main force behind participants’ learning on co-teaching; furthermore, such comparisons enable three main learning processes: reflection, negotiation and transfer, bearing mainly on teaching methods and materials and use of technology. Finally, there is evidence that occasional or ongoing team teaching (two instructors simultaneously in class) can enhance the effectiveness of co-teacher comparisons.